ROLE OF INFORMATION TECHNOLOGY AND BUSINESS ONLINE IN E-LOGISTIC SERVICES - PRETY DIAWATI; ABDUL RAHMAT (International Journal of Innovations in Engineering Research and Technology, 2021)
Logistics services have an important role in the context of a competitive global business. In addition, logistics has a strategic position and competitive advantage of a company. Most companies put logistics as the spearhead of their services. Information technology (IT) and the Internet have provided fundamental changes to the logistics system, namely by creating electronic logistics (e-logistics) that are practical, efficient and economical. Through e-logistics the company can expand its business more broadly and serve customers quickly. The purpose of this study is to explain new phenomena in e-logistics, namely the use of IT and the impact of online business growth on e-logistics services. However, e-logistics is a new paradigm in online service business in Indonesia.